PEDAGOGICAL ASPECTS OF EMOTIONAL INTELLIGENCE DEVELOPMENT IN STUDENTS (CAHIERS MAGELLANES-NS, 2024)
This article talks about the pedagogical aspects of developing emotional intelligence, which serves to increase the creative abilities of students. Analytical aspects of emotional processes in students are also highlighted.